Long-term safety assessment of live attenuated tetravalent dengue vaccines: deliberations from a WHO technical consultation. - Bentsi-Enchill, A; Schmitz, J; Edelman, R; Durbin, A; Roehrig, J; Smith, P; Hombach, J; Farrar, J (2013)
Dengue is a rapidly growing public health threat with approximately 2.5 billion people estimated to be at risk. Several vaccine candidates are at various stages of pre-clinical and clinical development. Thus far, live dengue vaccine candidates have been administered to several thousands of volunteers and were well-tolerated, with minimal short-term safety effects reported in Phase I and Phase II clinical trials. Based on the natural history of dengue, a theoretical possibility of an increased risk of severe dengue as a consequence of vaccination has been hypothesized but not yet observed. In October 2011, the World Health Organization (WHO) convened a consultation of experts in dengue, vaccine regulation and vaccine safety to review the current scientific evidence regarding safety concerns associated with live attenuated dengue vaccines and, in particular, to consider methodological approaches for their long-term evaluation. In this paper we summarize the scientific background and methodological considerations relevant to the safety assessment of these vaccines. Careful planning and a coordinated approach to safety assessment are recommended to ensure adequate long-term evaluation of dengue vaccines that will support their introduction and continued use.